On the Intersecting Family Process - Frieze, Alan; Bennett, Patrick; Newman, Andrew; Pegden, Wesley (The Electronic Journal of Combinatorics, 2024)
We study the intersecting family process initially studied in [Electron. J. Comb., 10:#R29 (2003)]. Here $k=k(n)$ and $E_1,E_2,…,E_m$ is a random sequence of $k$-sets from $\binom{[n]}{k}$ where $E_{r+1}$ is uniformly chosen from those $k$-sets that are not already chosen and that meet $E_i,i=1,2,…,r$. We prove some new results for the case where $k=cn^{1/3}$ and for the case where $k\gg n^{1/2}$.